THE INFLUENCE OF HYDROGEN ION CONCENTRATION ON THE INACTIVATION OF PEPSIN SOLUTIONS - Northrop, John H. (The Rockefeller University Press, 1920)
1. Pepsin in solution at 38°C. is most stable at a hydrogen ion concentration of about 10(–5) (pH 5.0). 2. Increasing the hydrogen ion concentration above pH 5.0 causes a slow increase in the rate of destruction of pepsin. 3. Decreasing the hydrogen ion concentration below pH 5.0 causes a very rapid increase in the rate of destruction of the enzyme. 4. Neither the purity of the enzyme solution nor the anion of the acid used has any marked effect on the rate of destruction or on the zone of hydrogen ion concentration in which the enzyme is most stable. 5. The existence of an optimum range of hydrogen ion concentration for the digestion of proteins by pepsin cannot be explained by the destruction of the enzyme by either too weak or too strong acid.